Nonclinical psychotic‐like experiences and schizotypy dimensions: Associations with hippocampal subfield and amygdala volumes. Issue 15 (24th July 2021) - Evermann, Ulrika; Gaser, Christian; Meller, Tina; Pfarr, Julia‐Katharina; Grezellschak, Sarah; Nenadić, Igor
Abstract: Schizotypy and psychotic‐like experiences (PLE) form part of the wider psychosis continuum and may have brain structural correlates in nonclinical cohorts. This study aimed to compare the effects of differential schizotypy dimensions, PLE, and their interaction on hippocampal subfields and amygdala volumes in the absence of clinical psychopathology. In a cohort of 367 psychiatrically healthy individuals, we assessed schizotypal traits using the Oxford‐Liverpool Inventory of Life Experiences (O‐LIFE) and PLE using the short form of the Prodromal Questionnaire (PQ‐16). Based on high‐resolution structural MRI scans, we used automated segmentation to estimate volumes of limbic structures. Sex and total intracranial volume (Step 1), PLE and schizotypy dimensions (Step 2), and their interaction terms (Step 3) were entered as regressors for bilateral amygdala and hippocampal subfield volumes in hierarchical multiple linear regression models. Positive schizotypy, but not PLE, was negatively associated with left amygdala and subiculum volumes. O‐LIFE Impulsive Nonconformity, as well as the two‐way interaction between positive schizotypy and PLE, were associated with larger left subiculum volumes. None of the estimators for right hemispheric hippocampal subfield volumes survived correction for multiple comparisons. Our findings support differential associations of hippocampus subfield volumes with trait dimensions rather than PLE, and support overlap and interactions between psychometric positive schizotypy and PLE. In a healthy cohort without current psychosis risk syndromes, the positive association between PLE and hippocampal subfield volume occurred at a high expression of positive schizotypy. Further studies combining stable, transient, and genetic parameters are required. Abstract : This study examined structural variation of the hippocampal subfields and the amygdala associated with subclinical dimensions of schizotypy, and psychotic‐like experiences (PLE). Volume alterations were associated with schizotypal traits, rather than PLE. In the left subiculum, the expression of PLE at higher positive schizotypy was associated with larger volumes.